Corrosion behavior of copper base alloy in present of straits of Malacca seawater - Chee, Chai Ling
The corrosion behavior of C2801 brass in presence of Straits of Malacca seawater, collected from different locations which are Klebang (Malacca), Tanjung Kling (Malacca), Tanjung Emas (Johore), Kuala Perlis (Perlis) and Straits of Malacca were investigated. The pH of seawater was determined and the C2801 brass in coupon with the dimension of 2 x 1.5 x 0.05cm were prepared for the test experiment, immersed in seawater for 10 days, 20 days, 30 days, 40 days, and 50 days.